SFTSV Infection Induced Interleukin-1β Secretion Through NLRP3 Inflammasome Activation - Liu, Jian-Wei; Chu, Min; Jiao, Yong-jun; Zhou, Chuan-Min; Qi, Rui; Yu, Xue-jie (Frontiers in Immunology, 2021)
Severe fever with thrombocytopenia syndrome virus (SFTSV) is an emerging tick-borne virus that causes hemorrhagic fever. Previous studies showed that SFTSV-infected patients exhibited elevated levels of pro-inflammatory cytokines like interleukin-1β (IL-1β), indicating that SFTSV infection may activate inflammasomes. However, the detailed mechanism remains poorly understood. Herein, we found that SFTSV could stimulate the IL-1β secretion in the infected human peripheral blood mononuclear cells (PBMCs), human macrophages, and C57/BL6 mice. We demonstrate that the maturation and secretion of IL-1β during SFTSV infection is mediated by the nucleotide and oligomerization domain, leucine-rich repeat-containing protein family, pyrin-containing domain 3 (NLRP3) inflammasome. This process is dependent on protease caspase-1, a component of the NLRP3 inflammasome complex. For the first time, our study discovered the role of NLRP3 in response to SFTSV infection. This finding may lead to the development of novel drugs to impede the pathogenesis of SFTSV infection.